A Note On "State Characteristics and the Location of Foreign Direct Investment within the United States" - Friedman, Joseph; Fung, Hung-Gay; Gerlowski, Daniel A.; Silberman, Jonathan (The Review of Economics and Statistics, 1996)
Joseph Friedman, Hung-Gay Fung, Daniel A. Gerlowski, Jonathan Silberman, A Note On "State Characteristics and the Location of Foreign Direct Investment within the United States", The Review of Economics and Statistics, Vol. 78, No. 2 (May, 1996), pp. 367-368